Changes in the Relative Abundance of Two Saccharomyces Species from Oak Forests to Wine Fermentations - Dashko, Sofia; Liu, Ping; Volk, Helena; Butinar, Lorena; Piškur, Jure; Fay, Justin C. (Frontiers in Microbiology, 2016)
Saccharomyces cerevisiae and its sibling species S. paradoxus are known to inhabit temperate arboreal habitats across the globe. Despite their sympatric distribution in the wild, S. cerevisiae is predominantly associated with human fermentations. The apparent ecological differentiation of these species is particularly striking in Europe where S. paradoxus is abundant in forests and S. cerevisiae is abundant in vineyards. However, ecological differences may be confounded with geographic differences in species abundance. To compare the distribution and abundance of these two species we isolated Saccharomyces strains from over 1,200 samples taken from vineyard and forest habitats in Slovenia. We isolated numerous strains of S. cerevisiae and S. paradoxus as well as small number of S. kudriavzevii strains from both vineyard and forest environments. We find S. cerevisiae less abundant than S. paradoxus on oak trees both within and outside the vineyard, but more abundant on grapevines and associated substrates. Analysis of the uncultured microbiome shows that both S. cerevisiae and S. paradoxus are rare species in soil and bark samples, but can be much more common in grape must. In contrast to S. paradoxus, European strains of S. cerevisiae have acquired multiple traits thought to be important for life in the vineyard and dominance of wine fermentations. We conclude that S. cerevisiae and S. paradoxus currently share both vineyard and non-vineyard habitats in Slovenia and we discuss factors relevant to their global distribution and relative abundance.